Video Assistant Refereeing (VAR) in the management of football matches: Are Football Fans Satisfied with this Technology - Karan, Kashveer (University of the Witwatersrand, Johannesburg, 2023)
Video assistant referee (VAR) is comprised of three people who work together to review controversial decisions made by the on-pitch referee in football matches. VAR is used in four match-changing situations; penalties, red cards, goals, and mistaken identity (Chandler, 2021; FIFA, 2021). There are various gaps in past literature; notably, previous studies have not explicitly focused on the emotional impact VAR is having on both players and fans. With the introduction of goal line technology and VAR, the International Football Association Board (IFAB) and Federation Internationale de Football Association (FIFA) finally made it possible for technology to assist referees in making decisions during games. Technology has long been a part of sports, and recently football has begun to modernize as well. In this research report, the impact that VAR has on football fans will be analyzed. The analysis will cover VAR's shortcomings, research into whether it is the best technology to correct human error, football fans' opinions of VAR, and whether AI and future technology might someday be used to assist referees in evaluating subjective in-game contentious situations. A quantitative methodology was used in this research report using the Qualtrics online survey to assist in identifying the satisfaction amongst footballing fans. This exercise had a successful population sample size of fifty-six people. A good mixture of views from both male and female representation, together with a very experienced age and number of years of watching football. This online survey was distributed to local footballing teams, supporter’s clubs, social clubs, and footballing communities. The overall results established is that the VAR technology and process is highly inconsistent, however this sample population see the merit in the VAR technology and believe there is a high potential for this technology to provide more fairness if certain aspects are changed. Some of the aspect which scored low in the survey, were related to the current process and how much this technology is impacting the games natural flow
A research article submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Master of Business Administration Johannesburg, 2023
Keywords: Video assistant referee (VAR); Referee; Football; Federation Internationale de Football Association (FIFA); Technology; UCTD; SDG-9: Industry, innovation and infrastructure